Effect of Psychoeducation on Postpartum Stress and Knowledge Related to Cyberbullying: An Experimental Study in Central Java - Nurul Jannatul Wahidah; Atriany Nilam Sari; Revi Gama Hatta Novika; Luluk Fajria; Rufidah Maulina; Siti Nurhidayati; Dara Dinanti; Elsa Rahmawati; Dewi Intisari (Masters Program in Public Health, 2026)
Background: Cyberbullying can trigger postpartum mother to experience anxiety and depression, which impacts their enthusiasm for caring for their babies. This study aimed to know the Impact of Psychoeducation on Postpartum Stress and Knowledge Related to Cyberbullying. Subjects and Method: This was a quasi-experimental study conducted in Surakarta, Central Java, Indonesia. A total of 86 postpartum mothers who experienced cyberbullying were included for study. The dependent variables were knowledge and postpartum stress. The independent variable was psychoeducation. Educational media video given to the respondent once a day for a week. Before and after the intervention, depression was measured using the Edinburgh Postnatal Depression Scale (EPDS). Data was analyzed using the Wilcoxon Test. Results: A total of 86 postpartum mothers had a high school education, were housewives, and married without prior depressive history. Knowledge of cyberbullying increased markedly, with the proportion of respondents in the